Legislation Related to the EU Mandatory Labeling System for Genetically Modified Foods and Enlightenments Drawn from It - ZHANG Jing, LUO Jiaoni (Shipin Kexue)
The labeling management of genetically modified foods (GMF) is a crucial link in ensuring food safety. The EU’s prudential supervision of the mandatory labeling of GMF provides a new path option for controlling safety risks. Continuously expanding the scope of GMF labeling, reducing labeling risk thresholds, establishing a whole-process traceability and genetically modified ingredient testing system, continuously optimizing the labeling system for GMF, and building a sound legal system concerning GMF labeling are the mandatory characteristics of EU GMF safety supervision. By reviewing the historical evolution of the EU GMF compulsory labeling system, we herein summarize its major legislative contents and the salient features of the related legal system, and put forward three legislative suggestions for improving the GMF labeling system in China. Furthermore, we propose that supporting measures should be established for traceability, testing and punitive relief. Our aim is to provide innovative ideas for solving the problems existing in China’s GMF labeling system.